1987
DOI: 10.1016/0014-5793(87)80400-3
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ uptake and IP3‐induced Ca2+ release in permeabilized human lymphocytes

Abstract: The 4SCa2 + uptake and 4sCa2 + release in saponin-permeabilized human lymphocytes were studied. An ATPdependent Ca 2 + uptake into a nonmitochondrial, intracellular Ca 2 + store is observed which is approx. 2 orders of magnitude greater than the ATP-independent Ca 2 + uptake. The Ca 2 + uptake is inhibited by vanadate, but it is insensitive to oligomycin and ruthenium red. IP 3 induces dose-dependent 4sCa2 + release. For half-maximum Ca 2 + release 0.25-0.5 pM IP 3 is required. The results of our studies sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
1999
1999

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Most previous studies of Ins(l,4,5)Pr-induced Ca 2+ release have utilized either cell-free systems or permeabilized cells. In general, these studies have shown that the intracellular Ca 2+ release is linearly proportional to the concentration of Ins(l,4,5)P3 for low doses and it plateaus for higher doses where most of the Ca 2+ pools were depleted by Ins(l,4,5)P3 (6,9,19,22,23,30,33,38,41,45,56,61). We have observed both linear and log-linear responses that do not appear to be correlated with the amount of Ins(1,4,5)P3 injected.…”
Section: Comlmrison To Previous Studies Of Ca ~" Releasementioning
confidence: 98%
“…Most previous studies of Ins(l,4,5)Pr-induced Ca 2+ release have utilized either cell-free systems or permeabilized cells. In general, these studies have shown that the intracellular Ca 2+ release is linearly proportional to the concentration of Ins(l,4,5)P3 for low doses and it plateaus for higher doses where most of the Ca 2+ pools were depleted by Ins(l,4,5)P3 (6,9,19,22,23,30,33,38,41,45,56,61). We have observed both linear and log-linear responses that do not appear to be correlated with the amount of Ins(1,4,5)P3 injected.…”
Section: Comlmrison To Previous Studies Of Ca ~" Releasementioning
confidence: 98%
“…EGTA (3 mM) was used in some experiments to lower extracellular [Ca 2ϩ ] i to 150 nM. IP 3 -mediated Ca 2ϩ release in T cells was carried out after permeabilizing the cells with saponin (150 µg/ml), as described earlier (15) [Ca 2ϩ ] i in T cells were calculated over the period of 300 s starting from the time of concanavalin A (Con A) stimulation. In the present study, we determined the effects of various Con A concentrations on T cell [Ca 2ϩ ] i elevation and found T cell stimulation to be maximal at the 100-µg/ml concentration.…”
Section: Methodsmentioning
confidence: 99%